Isolated Foveal Hypoplasia: Tomographic, Angiographic and Autofluorescence Patterns - Ágata Mota; Sofia Fonseca; Ângela Carneiro; Augusto Magalhães; Elisete Brandão; Fernando Falcão-Reis (Case Reports in Ophthalmological Medicine)
Purpose. To report clinical aspects, tomographic, angiographic, and autofluorescence patterns of two cases of isolated foveal hypoplasia. Methods. Foveal hypoplasia was found in a 23-year-old male patient and in a 64-year-old woman with impaired visual acuity of unknown etiology that remained unchanged for years. Results. In the first case, spectral-domain optical coherence tomography (SD-OCT) showed reduced foveal pit and continuity of inner retinal layers in the fovea. Photoreceptor layer had a normal thickness centrally. The foveal avascular zone (FAZ) was absent in the flourescein angiogram (FA). Fundus autofluorescence showed reduced foveal attenuation of autofluorescence. In the second patient, there was the same pattern in SD-OCT, with normal aspect in FA and only a slightly reduced foveal attenuation of autofluorescence. Conclusion. OCT, as a noninvasive and quick method, is helpful in the diagnosis of foveal hypoplasia. FA and fundus autofluorescence were less sensitive.